Ragapadmi and the First Leper: A Critical History of Leprosy Transmission in Madura, Indonesia - Romadhon, Dimas Iqbal (My University, 2018)
This thesis explores the interconnections between oral traditions and global health issues around leprosy. A folktale from Madura Island, Indonesia, telling about a princess named Ragapadmi who was expelled from her palace due to suffering leprosy, is the main focus in this study. The area studied, Madura Island, Indonesia, is known as one of the highest leprosy endemic areas in the world, which places Indonesia in the third place of international leprosy rankings in 2015. In this thesis, I study the movement of the Ragapadmi story from an oral tradition, which contains selected memories from the past time in Madura, to documented publications that were used by the Dutch administrators as a part of health propaganda to natives’ unique perceptions regarding leprosy which gives a stigma-free environment for leprosy sufferers in Madura. Studying this tongue to paper to mindset movement of a folktale, as I found during this study, is beneficial for the development of medical studies, specifically in the sub-fields of epidemiology, health propaganda and medical ethnology.
Thesis (Master's)--University of Washington, 2018
Keywords: Folktale; Indonesia; Leprosy; Madura; Ragapadmi; Southeast Asian studies; Public health; Folklore; Southeast Asia studies